Prognostic Value of Completion Lymph Node Dissection on Melanoma Patients with Positive Sentinel Lymph Node Biopsy: A Meta-analysis - LANG Zhongliang (Zhongliu Fangzhi Yanjiu, 2018)
Objective To assess the prognostic value of completion lymph node dissection on melanoma patients with positive sentinel lymph node biopsy. Methods We searched PubMed, Embase, Cochrane Library, CNKI, Wanfang and the reference trace for relevant literature. Meta-analysis was applied for patients' survival. Results A total of 10 clinical trials were included. There was no significant difference between the completion lymph node dissection group and the lymph node observation group in melanoma specific survival (HR: 0.99, 95%CI: 0.86-1.14, P=0.89), recurrence-free survival (HR: 0.89, 95%CI: 0.72-1.08, P=0.24) or distant metastasis-free survival (HR: 1.03, 95%CI: 0.89-1.20, P=0.71). Conclusion Completion lymph node dissection could not benefit the survival of melanoma patients with positive sentinel lymph node biopsy.